1984
DOI: 10.1111/j.1440-0960.1984.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Multiforme: Epidemiology, Clinical Characteristics and Natural History in Fifty‐nine Patients

Abstract: In this paper we report fifty-nine patients with erythema multiforme. Thirty-four of the patients were classified as erythema multiforme major (EM major) or StevensJohnson syndrome and the other twenty-five erythema multiforme minor (EM minor). The overall features of this group of fifty-nine patients are discussed and the significant differences between the two sub-groups (EM major and EM minor) highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…These lesions may remain localized to extremities or may become generalized with involvement of oro/genital mucosa and conjunctiva. When mucosal surfaces are involved, it is called as SJ Syndrome and manifests as rhinitis, vulvo-vaginitis and balanitis (7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…These lesions may remain localized to extremities or may become generalized with involvement of oro/genital mucosa and conjunctiva. When mucosal surfaces are involved, it is called as SJ Syndrome and manifests as rhinitis, vulvo-vaginitis and balanitis (7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study the incidence of EM minor is higher than EM major, because in most of the cases aetiological factor was herpes simplex which usually produces EM minor and is a fairly common infection even among healthy people. According to the study of Ting HC and Adam et al 5 the incidence of EM major was higher than EM minor. According to the study of Ashby & Theresa et al 3 the incidence of EM major is higher than EM minor.…”
Section: Clinical Typesmentioning
confidence: 92%
“…Female to Male ration was 1.6:1. The study of Ting HC and Adam BA et al 5 showed male preponderance in EM major and female preponderance in EM minor.…”
Section: Sex Incidencementioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have reported the annual incidence rates of Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN), peaking in the second decade of life, with a seasonal spring predominance (1)(2)(3)(4), but these results are limited because of small sample sizes within a few hospital catchment areas between the 1960s and 1990s (1)(2)(3)(4). Furthermore, surveys of SJS/TEN at the national level have not been conducted in the United States.…”
mentioning
confidence: 99%